THEORETICAL ESTIMATE OF LANDFILL GAS GENERATION OF THE FUTURE LANDFILL IN JI-PARANÁ – RO - Necker, Helder Sumeck; Rosa, Ana Lúcia Denardin da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The final destination of the urban solid waste stills a problem in the bigger part of Brazil, principally, in regions north and northeast. In the city of Ji-Paraná – RO, the current final destination of the solid waste don’t happens in a correct way, and that the project of construction of a landfill for the city already exists and should starts soon. Beyond the most appropriate way of urban solid waste final destination, the landfills can be a way of obtain energy, because of the great generation of landfill gas, that presents in their composition methane, one gas with a huge energetic potential. Therefore this work, search to estimate the generation of landfill gas in the landfill that will be built in Ji--Paraná, based on two methods: Inventory Method and Project Method. The values founded gets around 5.8 million m3of landfill gas in a year and the potential generation of the solid waste founded were nearly of 216 m3of landfill gas for ton of solid waste. In the firsts years of operation, the energetic potential of the landfill was estimated in 144 MW per month and after near then a decade of operation, the energetic potential could reach 432 MW per month e could provide electricity for about of 2.800 houses.